Monsoons, Upwelling, and the Deoxygenation of the Northwestern Indian Ocean in Response to Middle to Late Miocene Global Climatic Shifts. Issue 2 (5th February 2020) - Bialik, Or M.; Auer, Gerald; Ogawa, Nanako O.; Kroon, Dick; Waldmann, Nicolas D.; Ohkouchi, Naohiko
Abstract: Today, upwelling along the Oman margin in the Arabian Sea is governed by the South Asian Monsoon winds. The Oman upwelling results in the formation of an oxygen minimum zone (OMZ) spanning across the Arabian Sea and large parts of the Indian Ocean. While these conditions are recorded as early as the middle Miocene ( 15 Ma), the long‐term dynamics of upwelling in the Arabian Sea are as of yet poorly constrained during the middle to late Miocene. Here, we use organic and inorganic proxies combined with sedimentary and paleontological records to constrain the evolution of upwelling at Ocean Drilling Program Site 722B between 15 and 8.7 Ma. Our record shows that Mn depletion occurred at 14.5 Ma, likely due to regionally confined OMZ formation at that time. Biogenic silica accumulation intensified between 12.5 and 11 Ma. The δ 15 N values (>6‰) provide evidence for the onset of at least intermittent denitrification between 11 and 9.5 Ma during the apex of the global "carbonate crash." Our data demonstrate that upwelling and OMZ intensity in the Arabian Sea were linked to the reorganization of the Indian Ocean circulation system and South Asian Monsoon during the Miocene. The initiation of these systems occurred once the regional tectonic configuration (i.e., the uplift of the Tibetan Plateau 25 Ma and the closure of the Tethyan seaway 20 Ma) was in place. The subsequent development of monsoonal upwelling after 14 Ma responded to latitudinal shifts in climatic belts following the progressive Miocene glaciation of Antarctica. Key Points: We re‐evaluate the Miocene evolution of upwelling and oxygen depletion in the Western Arabian Sea, using a multiproxy approach We demonstrate that upwelling and oxygen depletion underwent a gradual evolution and intensification through the middle and late Miocene Upwelling and oxygen minimum zone state are linked to Miocene climatic shifts, apex between 11 and 9 Ma, marked by water body denitrification